MANAGEMENT OF HIJRAH COMMUNITY ACTIVITIES IN SUBANG REGENCY - Windia Windia; Conit Haq Zuwizat; Jojo Jojo (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2024)
This study aims to explore and analyze the management of activities within Hijrah communities in Subang Regency, as well as identify the factors influencing their effectiveness. Utilizing a qualitative approach with a case study method, the research provides an in-depth and contextual understanding of these phenomena. Data was gathered from four active Hijrah communities: Generasi Islam Urang Subang (Genius), Pemuda Cinta Islam (Peci), Komunitas Pejuang Akherat (Qopeah), and Majelis Istiqomah (Mistiq). The study employed several data collection techniques, including in-depth interviews with community members and leaders, participatory observation, and documentation analysis. The thematic analysis was used to identify, analyze, and report patterns within the data. The results indicate that effective community management is significantly influenced by strong leadership, active member participation, and external support from society and government. Additionally, well-organized management structures, innovative and relevant programs, regular leadership training, and efficient resource management were found to be critical for the success of these communities. The study concludes with recommendations for improving the management of Hijrah community activities, such as developing engaging programs, securing alternative funding sources, building strong external relationships, and conducting continuous evaluations to enhance activity management.